2003
DOI: 10.1002/chp.1340230204
|View full text |Cite
|
Sign up to set email alerts
|

Predicting career decisions in primary care medicine: A theoretical analysis

Abstract: Entering the 1960s, more than half of the medical doctors in the United States were family physicians, pediatricians, or general internists. Today, about one-third of all U.S. physicians are primary care practitioners. Although opinions vary on the optimal ratio of primary care to specialty physicians, in the mid-1990s, the consensus among leaders in medicine was that more primary care physicians would be needed to ensure access to quality care. The target output of graduates was set for a minimum of 50% prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
(5 reference statements)
1
10
0
4
Order By: Relevance
“…There has been a wealth of research on medical students' career choices, particularly in terms of selecting primary care specialties or family medicine (Bland et al 1995;Connelly et al 2003;Jordan et al 2003;Lawson and Hoban 2003;Senf et al 2003;Wright et al 2004). Studies have found that both internal influences (e.g.…”
Section: Introduction Medical Career Orientationmentioning
confidence: 97%
“…There has been a wealth of research on medical students' career choices, particularly in terms of selecting primary care specialties or family medicine (Bland et al 1995;Connelly et al 2003;Jordan et al 2003;Lawson and Hoban 2003;Senf et al 2003;Wright et al 2004). Studies have found that both internal influences (e.g.…”
Section: Introduction Medical Career Orientationmentioning
confidence: 97%
“…Efforts to select and matriculate medical students who will practice in certain specialties or in medically underserved regions have met with mixed results. [4][5][6] Initiatives to increase access to undergraduate and graduate medical education will take years before the promised results of increased numbers of qualified physicians can be evaluated. Medical passports are likely to be limited to a small number of physicians practicing in a few countries.…”
Section: Norcini Et Almentioning
confidence: 99%
“…Various surveys have been used to study this issue, with questionnaire distribution beginning as early as matriculation into medical school (Scott et al, 2004). A pair of literature reviews have suggested that demographic factors including being female and older in age correlate with a desire to pursue primary care (Bland et al, 1995;Lawson and Hoban, 2003). In addition, personality variables such as maintaining a social orientation and a desire for a varied scope of practice have been indicated as potentially useful (Bland et al, 1995;Lawson and Hoban, 2003).…”
Section: Introductionmentioning
confidence: 97%